An Epidemiological Study of Hypertension and Its Risk Factors in Rural Population of Bangalore Rural District - S.Madhukumar; V.Gaikwad; Sudeepa D (Al Ameen Medical College, 2012)
Background: In developing countries like India the prevalence of non communicable diseases is slowly assuming an alarming proportions and Hypertension is the commonest NCD and it accounts for a large proportion of cardiovascular deaths. Objectives: To estimate the prevalence of Hypertension in rural areas of Bangalore. To assess the risk factors and its strength of association with Hypertension. To study the treatment seeking behavior in hypertensives. Study period: June 2008 to June 2009. Materials and Methods: A house to house survey was conducted and 1501 study subjects 15 years of age and above were screened in a village using a pre tested questionnaire. Two independent BP readings were taken in sitting position by visiting each participant at their home. Hypertension was defined using JNC7 criteria. It defines hypertension as blood pressure more than 140/90 mmHg. Statistical tests: Percentiles, chi square test. Results: Prevalence of Hypertension was 8.06%. There were various risk factors significantly associated with hypertension like age, sex, BMI, smoking, alcohol, salt intake etc. Conclusion: The overall prevalence was 8.06%. Of the 121 hypertension patients 104 (85.95%) were aware of their disease and only 68 (65.38%) were taking regular treatment.